Highly sensitive simultaneous quantification of indoxyl sulfate and 3‐carboxy‐4‐methyl‐5‐propyl‐2‐furanpropanoic acid in human plasma using ultra‐high‐performance liquid chromatography coupled with tandem mass spectrometry. Issue 10 (11th March 2022) - Oda, Ayako; Suzuki, Yosuke; Sato, Banri; Sato, Haruki; Tanaka, Ryota; Ono, Hiroyuki; Ando, Tadasuke; Shin, Toshitaka; Mimata, Hiromitsu; Itoh, Hiroki; Ohno, Keiko
Abstract : Indoxyl sulfate and 3‐carboxy‐4‐methyl‐5‐propyl‐2‐furanpropanoic acid are uremic toxins that accumulate in renal failure and have been reported to decrease the activities of the drug‐metabolizing enzyme cytochrome P450 3A and the drug transporter organic anion transporting polypeptides 1B, respectively. In this study, we established and validated an assay for simultaneous quantification of indoxyl sulfate and 3‐carboxy‐4‐methyl‐5‐propyl‐2‐furanpropanoic acid in human plasma. The samples were pretreated by solid‐phase extraction, and measured by ultra‐high‐performance liquid chromatography–tandem mass spectrometry. The validation results for this assay were within the acceptable limits recommended by the US Food and Drug Administration, with a lower limit of quantitation of 0.05 μg/mL for both indoxyl sulfate and 3‐carboxy‐4‐methyl‐5‐propyl‐2‐furanpropanoic acid. Recovery rates of indoxyl sulfate and 3‐carboxy‐4‐methyl‐5‐propyl‐2‐furanpropanoic acid corrected by internal standard were 100.7–101.9 and 100.2–101.3%, respectively. Matrix effects of indoxyl sulfate and 3‐carboxy‐4‐methyl‐5‐propyl‐2‐furanpropanoic acid corrected by internal standard were 101.1–105.5 and 97.0–103.8%, respectively. The validated assay was used to analyze indoxyl sulfate and 3‐carboxy‐4‐methyl‐5‐propyl‐2‐furanpropanoic acid concentrations in the plasma samples of healthy volunteers and patients with chronic kidney disease. All the measured plasma indoxyl sulfate and 3‐carboxy‐4‐methyl‐5‐propyl‐2‐furanpropanoic acid concentrations were within the calibration ranges. This novel method may contribute to predicting the activities of drug‐metabolizing enzymes and drug transporters in individual patients.